GAMBARAN TINGKAT PENGETAHUAN PERAWAT TENTANG TRIASE DALAM MENGHINDARI PENINGKATAN ANGKA KECACATAN DAN KEMATIAN DI INSTALASI GAWAT DARURAT RUMAH SAKIT AMINAH - Ruli Setiyawan; Muhammad Taufik Daniel Hasibuan (Universitas Pahlawan Tuanku Tambusai, 2022)
The Emergency Room (IGD) is a very important entry point for health services for patients who need urgent and emergency treatment and care, triage is a complex decision-making process in order to determine which patients are at risk of dying, at risk of disability, or are at risk of worsening the clinical state. According to the data that the researchers got from one of the emergency room installations of a type C private hospital in the South Tangerang area which used the Australian Triage Scale (ATS) triage system, from October to November 2020, 1,036 patients went to the emergency room. At this stage, the knowledge of nurses about triage and the ability of emergency nurses plays an important role in reducing the number of disabilities and deaths in the ER, selecting the right patient according to the response time and actions that must be taken will reduce the number of disabilities and deaths in the ER. This study aims to analyze and describes the knowledge of nurses about triage in avoiding an increase in the number of disabilities and deaths in the emergency room at Aminah hospital. This research design used a descriptive design with total sampling. This research was conducted with a questionnaire consisting of 21 questions. The result of this research was that the category of most knowledge of nurses in the IGD Aminah Hospital was a sufficient category as much as 59%, then good as much as 28% and the last category was lacking as much as 13%. Keywords: Nurse Knowledge Level, Triage, Emergency Room